Invasive Sinu-Naso-Orbital Aspergillosis Following Dacryocystorhinostomy In An Immunocompetent Patient: A Rare Case Report And Literature Review (Bangladesh Journal of Neurosurgery, 2023)
Background: Invasive sino-naso-orbital aspergilloma is a rare disease with variable clinical features but in an immunocompetent patient it is rarely considered and often resulted in poor prognosis due to its diagnostic and therapeutic challenge. In this article we reported a rare case of invasive sinu-naso-orbital aspergillosis with intracranial extension following dacryocystorhinostomy (DCR). To our knowledge this is the only reported case in last 109 years.Case Description: A 61 years old normotensive non diabetic male referred to us from an ophthalmologist with the complaints of retro-orbital pain followed by progressive dimness of vision later blindness on right eye after dacryocystorhinostomy.Diagnosis and Intervention: His MRI reveals an isointense lesion in T1W and T2W image in right maxillary, ethmoidal sinus with orbital and retro-orbital and intracranial extension with heterogeneous contrast enhancement. Radiologist suggested a case of inflammatory pseudotumor and initially he was treated with steroid, due to lack of clinical response later antifungal was given but patient still was nonresponsive. The patient underwent right pterional craniotomy for biopsy and optic nerve decompression. Histopathology revealed aspergillus infection.  Post-operatively he was treated with voriconazole.Lessons: Invasive sino-orbital aspergillosis is rare in immunocompetent patients. Early diagnosis is critical for successful management. Due to difficulty of diagnosis and higher mortality and morbidity, our recommendation is- ‘a patient with nonspecific complaints or retro-orbital pain’ should prompt the physician to consider this diagnosis.Bang. J Neurosurgery 2022; 12(1): 47-52